SOCIAL SERVICES: ACHIEVEMENTS AND CHALLENGES IN THE ALBANIAN CONTEXT - Haxhiymeri, Edlira; Ndrio, Marina (Ревија за социјална политика/Journal of Social Policy, 2015)
The system of social services in Albania was totally transformed compared to the system that functioned during the communist time. Besides State, various groups of civil society, strategic partners, donors and international organizations played an important role in providing social services. The aim of this paper is a) to provide a general overview of the role of the actors that provide social services in Albania; b) to analyse the impact of decentralization and privatization of social services; c) to present evidence of achievements and challenges in the public and non public services. The paper is not intended to be a comprehensive one on the overall subject of the system of social services in Albania, but rather a review of services related to social protection of vulnerable groups, children and women support, services for the people with special needs. This paper is prepared based on documentation analysis (basic policy and strategic documents, legislation), interviewing and practical experience reflection. The documentation analysis has involved reviewing all readily available materials, like domestic government policy documents, official statistics, national reports, publications of the NGO that offer social services and research publications on social services. The method for analyzing the information was content analysis. Ten key actors in Albania were interviewed for the purpose of this research: five officials of the Ministry of Wellbeing and Youth and five representatives of NGO-s. The purpose of interviews was to gather information that is not publicly available and to generate insights on the issue of social service provision. It is a belief that the conclusions of this research will be a contribution to reshaping the role of all actors, increasing the role of the civil society and private providers of social services and improving the quality of social services in Albania.